The Prajuritan Dance Preservation of the Wahyu Kridha Budaya Association in Sumogawe Village, Getasan Sub-District, Semarang Regency - Septiani, Elza; Paranti, Lesa (Jurnal Seni Tari, 2024)
Prajuritan Dance of Wahyu Kridha Budaya Society is still active for three generations. The first generation is Mr. Noto Kayitno, the second generation is Mr. Srikoyo, and the third generation is Mr. Sumadi. Objectives, 1) to study the preservation of Prajuritan dance using aspects of protection, development, and utilization. 2) to describe the supporting and inhibiting factors of Prajuritan dance preservation of the Wahyu Kridha Budaya Association. The research used qualitative methods of emic and etic approaches. The research location is in Sumogawe Village, Getasan Sub-District. Data collection techniques include observation, interviews, and documentation. Data validity is in the form of source triangulation, technique triangulation, and time triangulation. The results showed, that 1) Preservation is carried out using three aspects in the form of protection from the village government, hamlet heads, associations, and the community. Development in terms of quality with the development of a variety of horse war movements, tidier makeup, and renewal of costumes, property, and musical instruments. Utilization is in the form of Prajuritan dance performances as entertainment and unification of the Magersari Hamlet community. 2) Supporting factors for the preservation of Prajuritan dance in the form of a sense of enthusiasm of members, financial assistance from the village government, and enthusiasm of the community in appreciation. The inhibiting factors are a vacuum during COVID-19, limited funds, and no social media to disseminate Prajuritan dance.